Strategic Formulation to Increase Room Occupancy Rate at Bali Palms Tabanan Bali - Christina Rosalia Sulestiyorini; Yeyen Komalasari; Christimulia Purnama Trimurti; R. Tri Priyono Budi Santoso (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to create a strategic plan for developing the potential occupancy rate at Bali Palms Tabanan Bali. This research was conducted to identify and analyze strengths, weaknesses, opportunities, and threats, as well as to determine the appropriate strategies for developing the occupancy rate potential at Bali Palms. The research was conducted through a survey. The formulation of the strategy is based on three stages: the input stage, the matching stage, and the decision stage. The analytical tools used are as follows: (1) Input stage: using External Factor Evaluation (EFE) Matrix, Internal Factor Evaluation (IFE) Matrix, and Competitive Profile Matrix (CPM); (2) Matching Stage: Strengths-Weaknesses-Opportunities-Threats (SWOT) Matrix, SPACE Matrix, BCG Matrix, IE Matrix; and Decision Stage using the Quantitative Strategic Planning Matrix (QSPM). The results of the research indicate that 4 priority strategies can be implemented, namely: Intensifying social media campaigns and collaborating with influencers to increase brand awareness of Bali Palms Tabanan; Conducting foreign language courses for local staff as part of a sustainable training program (CSR); Providing new and unique products that are different from competitors; and Developing a local supplier network to reduce additional costs and empower the local economy.